Determining the Production and Transport Cost for H2 on a Global Scale - Collis, Jason; Schomäcker, Reinhard (Frontiers in Energy Research, 2022)
Hydrogen (H2) produced using renewable energy could be used to reduce greenhouse gas (GHG) emissions in industrial sectors such as steel, chemicals, transportation, and energy storage. Knowing the delivered cost of renewable H2 is essential to decision-makers looking to utilize it. The cheapest location to source it from, as well as the transport method and medium, are also crucial information. This study presents a Monte Carlo simulation to determine the delivered cost for renewable H2 for any usage location globally, as well as the most cost-effective production location and transport route from nearly 6,000 global locations. Several industrially dense locations are selected for case studies, the primary two being Cologne, Germany and Houston, United States. The minimum delivered H2 cost to Cologne is 9.4 €/kg for small scale (no pipelines considered), shipped from northern Egypt as a liquid organic hydrogen carrier (LOHC), and 7.6 €/kg piped directly as H2 gas from southern France for large scale (pipelines considered). For small-scale H2 in Houston, the minimum delivered cost is 8.6 €/kg trucked as H2 gas from the western Gulf of Mexico, and 7.6 €/kg for large-scale demand piped as H2 gas from southern California. The south-west United States and Mexico, northern Chile, the Middle East and north Africa, south-west Africa, and north-west Australia are identified as the regions with the lowest renewable H2 cost potential, with production costs ranging from 6.7—7.8 €/kg in these regions. Each is able to supply differing industrially dominant areas. Furthermore, the effect of parameters such as year of construction, electrolyser, and H2 demand is analysed. For the case studies in Houston and Cologne, the delivered H2 cost is expected to reduce to about 7.8 €/kg by 2050 in Cologne (no pipelines considered, PEM electrolyser) and 6.8 €/kg in Houston.